Secure blockchain-based categorical information transaction and depository framework with identification enabled privacy and decentralized system - Ony, Shahinul Hoque; Rahman, Suraiya; Albi, Takrim Rahman (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.